Efficiency and Predictability of Coronal Maxillary Expansion Repercussion with the Aligners System: A Retrospective Study - Ana Sofia Rocha; Maria Gonçalves; Ana Catarina Oliveira; Rui M. S. Azevedo; Teresa Pinho (MDPI AG, 2023)
The Invisalign® system (SmartForce® G8) aims to guarantee aesthetics and provide good orthodontic treatment results. Dentoalveolar expansion is possible with clear aligners and can be used to correct dentoalveolar crossbite, resolve crowding or modify the arch shape. Despite the treatment's effectiveness, there is still disagreement among professionals concerning its true clinical potential. This study aimed to analyze the effectiveness and predictability of coronal tooth expansion movement in permanent dentition in patients who had completed the first phase of treatment with Invisalign® orthodontic aligners. Materials and Methods: The tooth movement tables of 75 previously selected cases were analyzed in terms of dental-arch width and expansion efficiency, through the Invisalign® platform, considering the pre-treatment (T0), planned treatment (TP) and post-treatment models (T1) using ClinCheck Pro® 6.0 software. All patients were treated by an orthodontic specialist and Invisalign® Diamond Provider in a private practice (T.P.). Results: Difference between T1 and T0: for each maxillary and mandibular measurement, there was a statistically significant difference between pre- and post-aligner treatment values. The greatest amount of expansion occurred in both the upper and the lower premolars. Difference between TP and T1: for each maxillary measurement, statistically significant differences were verified for the molar and canine. At the mandibular level, statistically significant differences were only verified in the first molar. Conclusions: The Invisalign® clear aligners are effective for simultaneous intra-arch expansion in both jaws.